IMPACTO DEL COMERCIO INTERNACIONAL EN EL CRECIMIENTO ECONÓMICO PARA LATINOAMÉRICA: UN ANÁLISIS UTILIZANDO TÉCNICAS DE COINTEGRACIÓN PARA EL PERIODO 1980-2015 - Erraes Cevallos, Jimmy Andrés (2019)
Latin American trade supports slight steps compared to other markets, this is due to its great dependence on the exploitation of its natural resources explicitly from oil, which means that given a fall in the price of a barrel of oil this will be reflected in an economic recession , so the objective of this research is to examine the incidence of international trade in the economic growth of Latin America, using cointegration techniques and error correction, with panel data. Countries have been classified by groups of countries according to their level of income in the period 1980-2015. For its realization, data from the World Bank (2017) have been taken. Likewise, this research is based on the review of previously analyzed literature, as well as the one proposed by Hernández (2002), where he maintains that foreign trade manages to increase the accumulation of the factor of production, physical and human capital, and the process of technological expansion, so it can be a growth accelerator mechanism. The results combine with the theoretical framework used and indicate that there is a significant positive relationship for the PIMA and PIMB this is because economic growth depends a lot on the generation of trade, since in turn if good numbers are not handled in the marketing of goods this will have an economic crisis, quite the opposite with the PIA that has a positive relationship but is not very strong compared to the other groups of countries, given that for this group of countries trade is not essential, Its source of income depends on other factors of the economy. In turn, a short and long term relationship was found between the analyzed variables.